2020
DOI: 10.3390/v12030276
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Antibodies with Antibody-Dependent Cellular Cytotoxicity Function

Abstract: Influenza causes millions of cases of hospitalizations annually and remains a public health concern on a global scale. Vaccines are developed and have proven to be the most effective countermeasures against influenza infection. Their efficacy has been largely evaluated by hemagglutinin inhibition (HI) titers exhibited by vaccine-induced neutralizing antibodies, which correlate fairly well with vaccine-conferred protection. Contrarily, non-neutralizing antibodies and their therapeutic potential are less well de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 142 publications
(222 reference statements)
0
22
0
1
Order By: Relevance
“…Here, we investigated the role of natural killer (NK) cells in mAb-mediated immunomodulation in infected mice. NK cells are FcγR-expressing innate effector cells that play a key role in the control of viral propagation upon mAb therapy through the killing of infected cells via ADCC [ 20 , 21 , 22 ]. In addition to their cytotoxic activity, NK cells display multiple immunomodulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigated the role of natural killer (NK) cells in mAb-mediated immunomodulation in infected mice. NK cells are FcγR-expressing innate effector cells that play a key role in the control of viral propagation upon mAb therapy through the killing of infected cells via ADCC [ 20 , 21 , 22 ]. In addition to their cytotoxic activity, NK cells display multiple immunomodulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, antibodies with RBS-blocking activity tend to induce less robust ADCC responses [ 115 , 116 , 117 , 118 ]. Nevertheless, antibody neutralization and induction of ADCC are not mutually exclusive and can operate synergistically [ 106 , 119 , 120 ]. Such synergy may also be balanced by antibody-dependent enhancement risks, such as enhanced infection of monocytes and myeloid dendritic cells as reported for anti-HA antibodies from macaques [ 121 ].…”
Section: Functionally Conserved Antibody Targets On Influenza Hemamentioning
confidence: 99%
“…The cross-linkage among the antigen, antibody and the effector cells triggers immune effector functions, including antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cell-mediated phagocytosis (ADCP) and complement-dependent cytotoxicity (CDC), which contribute to the clearance of virus-infected cells and virus particles (ADCP particularly) ( Figure 2 C). Many sources of evidence have shown that effector functions mediated by antibodies are critical for protection against influenza virus, human immunodeficiency virus and respiratory syncytial virus [ 117 , 118 , 119 ]. In addition, ADCC antibodies are associated with the clinical presentation of neonatal herpes simplex virus (HSV) infection [ 120 ] and are protective against HSV-1 and -2 in a mouse model of maternal immunization [ 121 ].…”
Section: Mda Interference: a Major Bottleneck For Ndv-vectored Vacmentioning
confidence: 99%